Analytical and Experimental Study of Micro Gas Turbine as Range Extender for Electric Vehicles in Asian Cities. (December 2017) - Tan, F.X.; Chiong, M.S.; Rajoo, S.; Romagnoli, A.; Palenschat, T.; Martinez-Botas, R.F.
Abstract: This paper presents the development of a Micro Gas Turbine (MGT) as range extender (RE) engine for electric vehicles (EV). A computational vehicle model was developed to analyze the impact of driving condition to the driving range of an EV and the sizing of range extender of the REEV, specifically for Malaysian Urban Drive Cycle (MUDC). The simulation shows that the driving range of an EV is greatly reduced when operating in MUDC condition. However, with a RE of as small as 10kW, the REEV could have the driving range which is comparable to conventional internal combustion engine (ICE) vehicle. Following this, a prototype MGT was designed and developed based on a commercial turbocharger and custom built combustor. Experiment of the MGT operating at self-sustaining operating point has been carried out to evaluate the system performance. The experimental data obtained from the MGT test rig is used to validate the computational model, which is the used to further explore the operational capability of the MGT as RE.